The Khohkoi Population: A Review of Evidence and Two New Estimates - Sumner La Croix (African Economic History Network (AEHN), 2018)
Fourie and Green construct estimates of the Khoikhoi population over the 1652- 1780 period using benchmarks for the initial and terminal Khoi populations and benchmarks for the punctuated population declines from smallpox epidemics in 1713 and 1755. I review the evidence underlying each of the four population benchmarks and argue for a revised 1780 benchmark. Qualitative evidence also points to a higher rate of population decline between 1652 and 1723 and a smaller rate of decline between 1723 and 1780. Using the Fourie-Green methodology and adopting 3 of their 4 population benchmarks, I develop two revised estimates of the Khoi population to supplement the original Fourie and Green estimates
Keywords: N01; N37; N57; 330; Demography; Cape colony; Khoi